2022
DOI: 10.1097/md.0000000000030506
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of post-infectious inflammatory reactions in a retrospective study of 3 common invasive bacterial infections in pediatrics

Abstract: Infectious diseases can result in unanticipated post-infectious inflammatory reactions (PIIR). Our aim was to explore PIIR in 3 frequent pediatric bacterial invasive infections in France by a retrospective monocentric study. We included children hospitalized between 2003 and 2012 for Streptococcus pneumoniae (SP), Neisseria meningitidis (NM), or Streptococcus pyogenes invasive infections. The PIIR had to have occurred between 3 and 15 days without fever despite an individually tailored antibiotic therapy. A de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…PIIR has been observed in different types of pediatric bacterial invasive infections. A French retrospective monocentric study identified 39 cases of PIIR in 189 children (20%) with various invasive infections due to S. pneumoniae , N. meningitis , or S. pyogenes 27 . Fever was the most frequent symptom of PIIR (87%), occurring on average 3.8 days after the end of the infectious episode.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…PIIR has been observed in different types of pediatric bacterial invasive infections. A French retrospective monocentric study identified 39 cases of PIIR in 189 children (20%) with various invasive infections due to S. pneumoniae , N. meningitis , or S. pyogenes 27 . Fever was the most frequent symptom of PIIR (87%), occurring on average 3.8 days after the end of the infectious episode.…”
Section: Discussionmentioning
confidence: 99%
“…27 pyogenes. 27 Fever was the most frequent symptom of PIIR (87%), occurring on average 3.8 days after the end of the infectious episode.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations